Peculiarities of vegetative regulation of heart rate in wrestlers of different age groups - Zapovitriana, E. B.; Korobeynikov, G. V.; Korobeinikova, L. G. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: the aim of the work was to study the characteristics of vegetative regulation of cardiac rhythm in athletes of high qualification of different age groups.